FRI0114 Rheumatoid arthritis related interstitial lung disease – relevance of lung function tests and high resolution computed tomography in a large multi centre series. (23rd January 2014) - Kelly, C.; Chan, E.; Nisar, M.; Arthanari, S.; Woodhead, F.; Dawson, J.; Sathi, N.; Ahmad, Y.; ,
Abstract : Background: Rheumatoid arthritis (RA) is associated with clinically relevant interstitial lung disease (ILD) in approximately 5% of patients. The natural history of the association has been shown to be poor: in a previous study mean survival was 3 years from diagnosis of RA-ILD [1 ]. The importance of high resolution computed tomography (HRCT) of the lung in assessing subtype of ILD has been established, and recent data suggests that extent of ILD may be an additional prognostic factor. Objectives: We have examined the subtype and extent of ILD by HRCT in a large multi centre series of patients with RA-ILD to assess the effects of each on outcome, and have related the disease extent to baseline pulmonary function. Methods: We collected data from five centres across the UK on 159 patients with both RA (EULAR 2010 criteria) and ILD (proven on HRCT) using a standard proforma over a period of 14 years. We assessed mortality and group demographics. We analysed the HRCT results for subtype (usual interstitial pneumonia = UIP, non specific interstitial pneumonia = NSIP, cryptogenic organising pneumonia = COP or mixed pattern =MP) and extent of lung involved (>20% = extensive; <20% = limited). We also collected data on baseline vital capacity (VC) and gas transfer (TLco), both expressed as percent predicted for age and gender. We examined the relationship between mortality, subtype and extent of RA-ILD. We also calculated and compared median values of VC and TLco in those with extensive vs limited disease. Results: A total of 32 deaths were recorded from 159 patients (20%) over 14 years, of which 15 (47%) were directly due to ILD. UIP was the predominant subtype (103) with smaller numbers of NSIP (39), MP(10) and COP (7). All cause mortality related to subtype, with UIP and MP having relative risks of 3.3 and 3.9 respectively compared to NSIP. Mean duration of RA was similar in the 90 patients with limited (7.2 years) and the 69 with extensive (7.0 years) disease at presentation, but extensive disease carried a relative risk of death of 2.0 compared to limited disease. Baseline median (range) VC was preserved at 101% (54-145%) in limited disease but reduced to 70% (44-117%) in those with extensive disease, while gas transfer was reduced in both limited [61%(33-106%)] and extensive [52%(22-109%)] disease. Conclusions: This is the largest study of RA-ILD in Europe. It confirms that the predominant pattern of ILD in RA is UIP and that the majority of patients have limited disease at presentation. It demonstrates that RA-ILD subtype and extent are both important predictors of mortality, with both UIP and extensive disease carrying significantly increased relative risks of all cause mortality. Although gas transfer is important in the diagnosis of ILD, VC appeared more useful in predicting disease extent on HRCT as it was relatively preserved in limited disease. References: Young A et al for ERAS. Mortality in rheumatoid arthritis. Rheumatology 2007; 46: 350-7. Disclosure of Interest: None Declared